Four new species of Neotropical spittlebugs (Hemiptera, Cercopidae, Tomaspidinae) - Costes,Danice H. (2004)
The following new species of South American Cercopidae, are described: Ischnorhina quadrimelasma sp. nov. (Bolivia), Laccogrypota quadrilineata sp. nov. (Bolivia), (Neolaccogrypota youngi sp. nov. (Peru), and Neosphenorhina schombergi sp. nov. (Brazil).